The Effect of Patient and Hospital Characteristics on Total Costs of Peripheral Bypass in New York State. (July 2021) - Ilonzo, Nicole; Goldberger, Cody; Hwang, Songhon; Rao, Ajit; Faries, Peter; Marin, Michael; Tadros, Rami
Introduction: With the aging U.S. population, peripheral vascular procedures will become increasingly common. The objective of this study is to characterize the factors associated with increased total costs after peripheral bypass surgery. Methods: Data for 34, 819 patients undergoing peripheral bypass surgery in NY State were extracted using the Statewide Planning and Research Cooperative System (SPARCS) database for years 2009-2017. Patient demographics, All Patient Refined Diagnostic Related Groups (APR) severity score, mortality risk, hospital volume, and length of stay data were collected. Primary outcomes were total costs and length of stay. Data were analyzed using univariate and multivariate analysis. Results: 28.1% of peripheral bypass surgeries were performed in New York City. 7.9% of patients had extreme APR severity of illness whereas 32.0% had major APR severity of illness. 6.3% of patients had extreme risk of mortality and 1 in every 5 patients (20%) had major risk of mortality. 24.9% of patients were discharged to a facility. The mean length of stay (LOS) was 9.9 days. Patient LOS of 6-11 days was associated with +2, 791.76 total costs. Mean LOS of ≥ 12 days was associated with + 27, 194.88 total costs. Multivariate analysis revealed risk factors associated with an admission listed in the fourth quartile of total costs (≥36, 694.44) for peripheral bypass surgery included NYC location (2.82, CI 2.62-3.04), emergency surgery (1.12, CI 1.03-1.22), extreme APR 2.08, 1.78-2.43, extreme risk of mortality (2.73, 2.34-3.19), emergency room visit (1.68, 1.57-1.81), discharge to a facility (1.27, CI 1.15-1.41), and LOS in the third or fourth quartile (11.09, 9.87-12.46). Conclusion: The cost of peripheral bypass surgery in New York State is influenced by a variety of factors including LOS, patient comorbidity and disease severity, an ER admission, and discharge to a facility.